Art and Architecture of Ireland Volume IV: Architecture 1600-2000 - Loeber, Rolf; Campbell, Hugh; Hurley, Livia; Montague, John; Rowley, Ellen (Art and Architecture of Ireland, 2015)
The most complete survey of architecture in Ireland ever published. The essays in this volume cover all aspects of Ireland's built environment, not only buildings but infrastructure, landscape development, public and private construction and much else. The volume challenges and expands the traditional understanding of Irish 'architecture', giving novel and exciting interpretations of the field and, by means of many striking illustrations, encourages us to think anew about the environment that surrounds us.